Hungarian Monitoring, 22 May 1990 . [Magyar rádiófigyelő], 1990. május 22 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Géza Szőcs elected senator in Romania - Romanian polls - Negotiations in Brussels about support for Hungary and Poland - NATO meeting in Brussels - Socialist International holds its meeting in Cairo - Tensions in the Baltic states - Schedule of Soviet economic reform - Railways strike in Poland Domestic Affairs: - Parliament to hear the PM's speech about the forthcoming government's program - Havel meets the representatives of Hungarians in Slovakia - Hungary opens a consulate in Zagreb - Hungarian citizens' plundering in Debrecen airport Economy: - Negotiations about the distribution of the assets of the National Confederation of Trade Unions Külpolitika: - Szőcs Géza szenátor Romániában - Román választási eredmények - Brüsszeli tárgyalások Magyarország és Lengyelország támogatásáról - NATO tanácskozás Brüsszelben - Kairóban ülésezik a Szocialista Internacionálé - Balti felszültségek - Szovjet gazdasági reform ütemterve - Lengyel vasutassztrájk Belpolitika: - Az Országgyűlés meghallgatta Antall József kormányprogramját - Havel fogadja a szlovákiai magyarság képviselőit - Magyar konzulátus nyílik Zágrábban - Magyar állampolgárok fosztogatják a debreceni repülőteret Gazdaság: - Tárgyalások a SZOT vagyonának elosztásáról